Genetic markers associated with resistance to beta-lactam and quinolone antimicrobials in non-typhoidal Salmonella isolates from humans and animals in central Ethiopia - Eguale, Tadesse; Birungi, Josephine; Asrat, Daniel; Njahira, Moses N.; Njuguna, Joyce N.; Gebreyes, Wondwossen A.; Gunn, John S.; Djikeng, Appolinaire; Engidawork, Ephrem (Springer, 2017)
Beta-lactam and quinolone antimicrobials are commonly used for treatment of infections caused by non-typhoidal Salmonella (NTS) and other pathogens. Resistance to these classes of antimicrobials has increased significantly in the recent years. However, little is known on the genetic basis of resistance to these drugs in Salmonella isolates from Ethiopia. Salmonella isolates with reduced susceptibility to beta-lactams (n = 43) were tested for genes encoding for beta-lactamase enzymes, and those resistant to quinolones (n = 29) for mutations in the quinolone resistance determining region (QRDR) as well as plasmid mediated quinolone resistance (PMQR) genes using PCR and sequencing. Beta-lactamase genes (bla) were detected in 34 (79.1%) of the isolates. The dominant bla gene was blaTEM, recovered from 33 (76.7%) of the isolates, majority being TEM-1 (24, 72.7%) followed by TEM-57, (10, 30.3%). The blaOXA-10 and blaCTX-M-15 were detected only in a single S. Concord human isolate. Double substitutions in gyrA (Ser83-Phe + Asp87-Gly) as well as parC (Thr57-Ser + Ser80-Ile) subunits of the quinolone resistance determining region (QRDR) were detected in all S. Kentucky isolates with high level resistance to both nalidixic acid and ciprofloxacin. Single amino acid substitutions, Ser83-Phe (n = 4) and Ser83-Tyr (n = 1) were also detected in the gyrA gene. An isolate of S. Miami susceptible to nalidixic acid but intermediately resistant to ciprofloxacin had Thr57-Ser and an additional novel mutation (Tyr83-Phe) in the parC gene. Plasmid mediated quinolone resistance (PMQR) genes investigated were not detected in any of the isolates. In some isolates with decreased susceptibility to ciprofloxacin and/or nalidixic acid, no mutations in QRDR or PMQR genes were detected. Over half of the quinolone resistant isolates in the current study 17 (58.6%) were also resistant to at least one of the beta-lactam antimicrobials. Acquisition of blaTEM was the principal beta-lactamase resistance mechanism and mutations within QRDR of gyrA and parC were the primary mechanism for resistance to quinolones. Further study on extended spectrum beta-lactamase and quinolone resistance mechanisms in other gram negative pathogens is recommended.